Effect of continuous aerobic exercise on endothelial function: A systematic review and meta-analysis of randomized controlled trials - Tao, Xifeng; Chen, Yiyan; Zhen, Kai; Ren, Shiqi; Lv, Yuanyuan; Yu, Laikang (Frontiers in Physiology, 2023)
Background: Current research suggests that continuous aerobic exercise can be effective in improving vascular endothelial function, while the effect between different intensities and durations of exercise is unclear. The aim of this study was to explore the effect of different durations and intensities of aerobic exercise on vascular endothelial function in different populations. Methods: Searches were performed in PubMed, Web of Science, and EBSCO databases. We included studies that satisfied the following criteria: (1) randomized controlled trials (RCTs); (2) including both an intervention and control group; (3) using FMD as the outcome measure; and (4) testing FMD on the brachial artery. Results: From 3,346 search records initially identified, 44 studies were eligible for meta-analysis. There was a significant effect of continuous aerobic exercise on improving flow-mediated dilation (FMD) [weighted mean difference (WMD), 2.25, (95% CI, 1.69 to 2.80), P < 0.00001]. Specifically, moderate-intensity [2.59 (1.84 to 3.35), P < 0.00001] and vigorous-intensity exercise [2.45 (1.52 to 3.39), P < 0.00001] significantly increased FMD. In addition, a longer duration [< 12 weeks, 2.25 (1.54 to 2.95), P < 0.00001; ≥ 12 weeks, 2.33 (1.64 to 3.02), P < 0.00001], an older age [age < 45, 2.09 (0.78 to 3.40), P < 0.002; 45 ≤ age < 60, 2.25 (1.49 to 3.01), P < 0.00001; age ≥ 60, 2.62 (1.31 to 3.94), P <0.0001], a larger basal body mass index (BMI) [20 < BMI < 25, 1.43 (0.98 to 1.88), P < 0.00001; 25 ≤ BMI < 30, 2.05 (1.16 to 2.95), P < 0.00001; BMI ≥ 30, 2.50 (1.36 to 3.63), P < 0.0001], and a lower basal FMD [4 ≤ FMD < 7, 2.34 (1.85 to 2.83), P < 0.00001; FMD < 4, 2.16 (0.54 to 3.78), P < 0.0001] were associated with larger improvements in FMD. Conclusions: Continuous aerobic exercise, especially moderate-intensity and vigorous-intensity aerobic exercise, contributed to improving FMD. The effect of continuous aerobic exercise on improving FMD was associated with duration and participant’s characteristics. Specifically, a longer duration, an older age, a larger basal BMI, and a better basal FMD contributed to more significant improvements in FMD.